Kinematic and kinetic analysis of the goalkeeper`s diving save in football - Ibrahim, R.; Kingma, I.; de Boode, V. A.; Faber, G. S.; van Dieën, J. H. (Journal of Sports Sciences, 2019)
Kinetics and full body kinematics were measured in ten elite goalkeepers diving to save high and low balls at both sides of the goal, aiming to investigate their starting position, linear and angular momentum, and legs' contribution to end-performance. Our results showed that goalkeepers adopted a starting position with a stance width of 33 ± 1% of leg length, knee flexion angle of 62 ± 18° and hip flexion angle of 63 ± 18°. The contralateral leg contributed more than the ipsilateral leg to COM velocity (p < 0.01), both for the horizontal (2.7 ± 0.1 m/s versus 1.2 ± 0.1 m/s) and for the vertical component (3.1 ± 0.3 m/s versus 0.4 ± 0.2 m/s). Peak horizontal and peak angular momenta were significantly larger (p < 0.01) for low dives than for high dives with a mean difference of 55 kg·m·s-1 and 9 kg·m2·s-1, respectively. In addition, peak vertical momentum was significantly larger (p < 0.01) for high dives with a mean difference between dive heights of 113 kg·m/s. Coaches need to highlight horizontal lateral skills and exercises (e.g. sideward push-off, sideward jumps), with emphasis on pushing-off with the contralateral leg, when training and assessing goalkeeper`s physical performance.